Christian-Muslim relations during the Crusades - Mallett, Alexander (Past imperfect (ARC Humanities Press), 2023)
The popular view of the Crusades is that of two zealous armies ranged against each other in a state of practically permanent warfare, lacking mutual respect, understanding, or co-operation. Scholars long ago replaced such ideas with a much more nuanced understanding, in which rulers from both sides could work together for mutual benefit, even while pretending to ascribe to the principles of crusade and jihad. This perspective, however, focused almost exclusively on the actions of the elites; the attitudes of those who made up the vast majority of the society in the Levant have been all but ignored. In a clear and accessible form, this book explores everyday relations and interactions between Christians and Muslims in the Levant during the Crusades, demonstrating that it was usually practicality rather than religious scruples that dictated their responses to the religious other.